PEMBUATAN KURVA ISODOSIS 2D UNTUK BERKAS ELEKTRON ENERGI 5 MeV MENGGUNAKAN PROFILE DOSE DAN KURVA PERCENTAGE DEPTH DOSE (PDD) UNTUK TREATMENT PLANNING SYSTEM RADIOTERAPI - Mahfudz Fauzan; Vincensius Gunawan; Choirul Anam (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Research has been done to make isodose curve of electron beam with the energy of 5 MeV. Isodosis curve performed using PDD curves and dose on broad Profile 10x10 cm2 field; 15x15 cm2; 20x20 cm2; 25x25 cm2, with a depth of 0.5 cm; 1.0 cm; 1.5 cm; 2.0 cm; 2.5 cm. The purpose of this study was to obtain 2D isodose curve shape can be applied to TPS in Radioteraphy.The method which was used to form the isodose curve using PDD curves and dose profiles was done by equalizing the data at each depth using interpolation techniques at intervals of 0.25 cm and normalized to a value of 1, and calculatd the dose at each pixel using the weighting technique that formed isodosis curve with the distribution each depth and broad field. The results show that the PDD curve formed using the interpolation does not affect the magnitude of the dose at different field wide, profile shaped dose showed a dose level at each different depth and normalized to a value of 1 to show the dose at the surface, the isodose curve formation can be applied to compare the isodose curve formed by TPS in Radiotherapy. Keywords: Radiotherapy, Treatment Planning System (TPS), isodose curve, Percentage Depth Dose (PDD), Profile dose